Serological heterogeneity among fimbrial antigens causing mannose-resistant hemagglutination by uropathogenic Escherichia coli. - Clegg, S (1982)
Serological agglutination tests were used to determine cross-reactivity among mannose-resistant fimbrial hemagglutinins of uropathogenic Escherichia coli. Of 47 E. coli strains demonstrating mannose-resistant activity, 12 were agglutinated by one fimbrial antiserum and two reached with a second serum. The mannose-resistant hemagglutinins (fimbriae) of urinary E. coli exhibit antigenic heterogeneity.